Productivity of dry seeded and transplanted rice (Oryza sativa) in aman season (Bangladesh Journal of Agricultural Research, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bjar.v39i1.20171 Bangladesh J. Agril. Res. 39(1): 185-187, March 2014